2018
DOI: 10.1111/nep.13059
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated variables of post‐dialysis fatigue: Results of a prospective multicentre study

Abstract: Post-dialysis fatigue is frequent and associated with age and ADL. Dialytic variables seem unrelated to PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 40 publications
(70 reference statements)
3
38
3
Order By: Relevance
“…Little is known about the determinants of recovery time [5][6][7]. Recently, we have demonstrated that recovery time is significantly associated with post-dialysis fatigue and that the severity of post-dialysis fatigue was negatively and weakly associated with the ultrafiltration rate (UFR) [8]. The association between a longer recovery time and a higher UFR has been shown by some authors but not by others [4,9].…”
Section: Introductionmentioning
confidence: 82%
“…Little is known about the determinants of recovery time [5][6][7]. Recently, we have demonstrated that recovery time is significantly associated with post-dialysis fatigue and that the severity of post-dialysis fatigue was negatively and weakly associated with the ultrafiltration rate (UFR) [8]. The association between a longer recovery time and a higher UFR has been shown by some authors but not by others [4,9].…”
Section: Introductionmentioning
confidence: 82%
“…At the time of inclusion in the study, patients underwent assessment of functional ability by the Katz ADL questionnaire and the Lawton and Brody IADL scale . Patients were subsequently categorized in ADL‐disabled (ADL = 0–5) or ADL‐competent (ADL = 6).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have demonstrated that PDF is highly prevalent among patients on chronic hemodialysis, and is strongly associated with time of recovery after hemodialysis (TIRD), older age, and lower functional ability . We also showed that the severity of PDF is independently associated with ADL (activity daily living) .…”
mentioning
confidence: 87%
“…The causes and the pathogenesis of PDF are essentially unknown and this is essentially due to the lack of adequate longitudinal studies. Furthermore, a few studies that have evaluated the demographic, clinical and laboratory variables associated with PDF have been conducted (Sklar et al 1996; Gordon et al 2011; Dubin et al 2013; Bossola et al 2018a). As a possible cause of PDF, it has been suggested that the osmolarity decrease occurring during dialysis may lead to brain swelling and associated headache, nausea, muscle cramps and fatigue (Sklar et al 1996, 1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, Dreisbach et al (1998) have shown that the intradialytic elevation of tumour necrosis factor‐α was significantly greater in patients with PDF than in those without. Interestingly, PDF has been was found to be significantly associated with symptoms of depression (Sklar et al 1996), disability (Bossola et al 2018a) and sedentary behaviour (Gordon et al 2011).…”
Section: Literature Reviewmentioning
confidence: 99%